Disadvantaged countries, sectors and regions in the Caribbean Community - Samuel, Wendell (JEWELL Consulting Services Frigate BayKN)
Discusses the concept of disadvantaged and the issues related to its measurement; the implications of the theory of economic integration for dislocation of economies, sectors and regions; the various measures which have been used to ameliorate the negative effects of economic integration internationally; and, the measures used in CARICOM to achieve the same end.